The hydrogeology of the Beaver Creek drainage basin, Larimer County, Colorado - Cerrilo, Lawrence Arnold, author; McCallum, M. E. (Malcolm E.), 1934-, advisor; Guy, Harold P., committee member; Waltz, James P., committee member (Colorado State University. Libraries, 1967)
Beaver Creek Basin is a glaciated basin of 20.5 square miles located in Larimer County, Colorado. It is comprised of four large sub-basins: Hourglass, Comanche Lake, Mummy, and Browns Lake, and two small subbasins. Two existing surface reservoirs, Comanche and Hourglass (for which adjudicated water rights are approximately 2,600 and 1,600 acre feet respectively) are located within the basin. The basement rocks in the basin consist of highly jointed granites, gneisses, and schists, overlain by glacial drift from four advances of Wisconsin glaciation (Bull Lake and Pinedale I, II, and III) and two advances of Recent age (Temple Lake and Gannett Peak). Extensive outwash deposits associated with the drift in the main basin, and especially in the vicinity of the reservoirs, are estimated to be 60 to 110 feet thick. These materials result in high infiltration rates to ground water within the main basin. Surface water losses to ground water in the subbasins are due primarily to infiltration from small lakes, ponds, and swampy areas retained by moraines of the Pinedale III advance. Infiltration rates in the vicinity of the reservoirs range from 4 inches per hour to more than 23.4 inches per hour. Loss of surface water in this area is a direct result of high infiltration.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Geology -- Colorado -- Larimer County; Hydrology